SAFETY AND EFFICACY OF THREE TREATMENT REGIMENS OF R-CHOP, E-CHOP, AND R-CHOEP IN NON-HODGKIN LYMPHOMA CANCER PATIENTS - Ahmad, Ayaz; Daud Ali, Mohammad; Almahmoud, Sana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was designed to investigate safety, efficacy of different regimens such as R-CHOP, E-CHOP, and R-CHOEP used in the treatment of in non-Hodgkin lymphoma (NHL) cancer patients. Methods: Available and required data of 64 NHL cancer patients were collected. Data were related to demography of patients, name of the drug, dose, route, frequency, duration of therapy, and investigational reports. Results: This study showed some variation and similarities in different regimens. Arm-A (R-CHOP) and Arm-B (E-CHOP) showed similar result for Eastern Cooperative Oncology Group (ECOG) score 2 but showed different result of ECOG score 0 and 1. High percentage of patient was taken in Arm-A and Arm-B as compared to Arm-C (R-CHOEP) for ECOG score 2. Surprisingly, it was found that very few percentages of patients showing progressive disease during R-CHOEP as compared to R-CHOP, E-CHOP therapy. Conclusion: From this study, it was concluded that Arm-C (R-CHOEP) showed better result in comparison of Arm-A (R-CHOP) and Arm-B (E-CHOP). As far as toxicity is concern, early detection and personalized management may improve clinical outcome and tolerance.